Strategies Developed by Toxoplasma gondii to Survive in the Host - Zhu, Wanbo; Li, Jingyang; Pappoe, Faustina; Shen, Jilong; Yu, Li (Frontiers in Microbiology, 2019)
One of the most successful intracellular parasites, Toxoplasma gondii has developed several strategies to avoid destruction by the host. These include approaches such as rapid and efficient cell invasion to avoid phagocytic engulfment, negative regulation of the canonical CD40-CD40L-mediated autophagy pathway, impairment of the non-canonical IFN-γ-dependent autophagy pathway, and modulation of host cell survival and death to obtain life-long parasite survival. Different virulent strains have even evolved different ways to cope with and evade destruction by the host. This review aims to illustrate every aspect of the game between the host and Toxoplasma during the process of infection. A better understanding of all aspects of the battle between Toxoplasma and its hosts will be useful for the development of better strategies and drugs to control the parasite.